Conservation laws of the J-integral type in micropolar elastostatics - Jarie, J.
Noether's theorem is used in an appropriate generalized form to deduce cnnservation laws of the J-integral type in the linear elastostatics of micropolar continua. The 1-parameter family of transformations associated with these conservation laws is determined on the basis of physically reasonable assumptions.
Keywords: STRESSES